Perspektif Pemasaran Media Sosial, Live Streaming, dan Penilaian Online Pelanggan Pada Minat Beli The Originote: Studi Pada Followers Instagram - Nada Adilah; Agung Sedayu (Jurnal Riset dan Inovasi Manajemen, 2024)
As marketing strategies evolve, digital marketing is becoming increasingly integral to contemporary marketing approaches. Various promotional tactics, including social media marketing, live streaming, and online customer evaluations, are being utilized by companies to attract consumer interest in purchasing products. This study aims to examine the impact of social media marketing, live streaming, and online assessments on purchasing interest in The Originote products on the Shopee platform. The study population consists of The Originote's Instagram followers, with a sample size of 117 respondents. Data analysis is conducted using SPSS 26, encompassing validity and reliability assessments, classical assumption tests, multiple linear regression analysis, f-tests, and t-tests. The findings of the study suggest that while social media marketing (X1) does not significantly influence purchasing interest, live streaming (X2) and Customer online Review (X3) exhibits a significant impact on purchasing interest.